Real-World Effects of Chinese Herbal Medicine for Idiopathic Membranous Nephropathy (REACH-MN): Protocol of a Registry-Based Cohort Study - Yang, Lihong; Chen, Xueyin; Li, Chuang; Xu, Peng; Mao, Wei; Liang, Xing; Zuo, Qi; Ma, Weizhong; Guo, Xinfeng; Bao, Kun (Frontiers in Pharmacology, 2022)
Introduction: Some encouraging findings of Chinese herbal medicine (CHM) in management of idiopathic membranous nephropathy (IMN) obtained in the setting of clinical trials are hard to validate in the daily clinical practice due to a complicated treatment scenario of CHM in practice. The primary objective of this registry is to provide a description of treatment patterns used in management of IMN and assess clinical remission in daily practice in a Chinese population sample with IMN. Methods and analysis: This is a prospective, multicentre cohort which will comprise 2000 adults with IMN regardless of urinary protein levels that will be recruited from 11 nephrology centres across China. The participants will be followed for up to at least two years. Primary outcome is composite remission (either complete remission or partial remission) 24 months after enrolment. The secondary outcomes are complete remission, partial remission, time to remission, no response, relapse, proteinuria, annual change of glomerular filtration rate, antibodies against PLA2R, and composite endpoint of 40% reduction of glomerular filtration rate, doubling of serum creatinine, end-stage renal disease and death. Propensity score analysis will be used for matching and adjustment. Ethics and dissemination: This study has been approved by the Ethics Committee of Guangdong Provincial Hospital of Chinese Medicine (BF2020-094-01). Results of the study will be published in both national and international peer-reviewed journals, and presented at scientific conferences. Investigators will inform the participants as well as other IMN patients of the findings via health education. Study registration: ChiCTR2000033680 (prospectively registered)